Comparison of Morphological and Anatomical Characteristics of Rice Paddy Herb (Limnophila aromatica Merr), Brahmi (Bacopa monnieri (L.) Wettst) and Giant Bacopa (Bacopa caroliniana (Walt) Robins) - Maikami, Mattanaporn; Nilrit, Phimnara (Thai Journal of Science and Technology, 2024)
Identification of local vegetables and herbs using only morphological characteristics do not probably sufficient. It must rely on studies in other fields. Plant anatomy is another tool that efficient support to classify plant species. Rice paddy herb, brahmi and giant bacopa are plants in the same family and habitat. It is probably confused with taking advantage of these plants. Rice paddy herb, brahmi and giant bacopa were studied the morphology of stems, leaves, and flowers using a stereo microscope. Additionally, they were studied the anatomy of leaf surface and stem tissues using a light microscope to compare and classify these plant species. When considering stems and leaves covered with trichome can be classified, the brahmi stem is glabrous. And then, leaf shape is able to classify rice paddy herb and giant bacopa apart. In view of flower, the sepal characteristic is capable of separating rice paddy herb from the other 2 species. And subsequently, brahmi and giant bacopa can be identified by the color at the base of the petals. In the case of anatomical characteristics, the layer of air space divided giant bacopa from rice paddy herb and brahmi. After that collenchyma tissue of the stem was applied to sort between rice paddy herb and brahmi. Rice paddy herb obviously demonstrates collenchyma tissue. Morphological and/or anatomical characteristics are able to classify rice paddy herb, brahmi and giant bacopa. Additionally, these knowledges expand the limited anatomical information on this plant group, application to other related study fields as well as leading to the development and conservation of plant genetic resources for further efficiency.